A Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials and their preparation methods and applications
The Ti3C2Tx/TiO2 two-dimensional nanosheet material prepared through etching and voltage oxidation steps solves the problem of difficulty in controlling the degree of oxidation when combining MXene with TiO2 in the existing technology, and achieves the preparation of photo/electrocatalytic materials with uniform structure and excellent performance. , with the ability to efficiently degrade water pollutants.
Patent Information
- Application Number
- CN202310095692.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-10
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-02-10
AI Technical Summary
The prior art is difficult to effectively combine the excellent properties of MXene and TiO2 to build a photo/electrocatalytic material with excellent performance, and it is difficult to control the material structure and oxidation degree during the oxidation process, resulting in unstable material performance.
By etching Ti3AlC2 MAX powder into Ti3C2Tx MXene nanosheets in a hydrofluoric acid aqueous solution, and through ultrasonic dispersion and voltage oxidation steps, Ti3C2Tx/TiO2 two-dimensional nanosheet materials with uniform structure are gradually prepared. This method is gentle and controllable, and can flexibly adjust the TiO2 content to match different application requirements.
It has achieved fast, low energy consumption and large-scale preparation of Ti3C2Tx/TiO2 two-dimensional nanosheet materials with uniform structure, avoiding material structural damage and excessive oxidation, and has excellent photo/electrocatalytic properties, especially against water pollution under ultraviolet light irradiation. The material has efficient degradation ability.
Smart Images

Figure CN116037179B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of nanomaterials and specifically relates to a Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet material, preparation method thereof and application thereof in preparing water pollutant degradation material. Background Art
[0002] MXene is a new type of two-dimensional material discovered in recent years. It has a high specific surface area, good conductivity and hydrophilicity. It is one of the most promising two-dimensional nanomaterials. MXene is a layered structure material composed of transition metal nitrides, carbides or carbonitrides. Its chemical formula can be expressed as n+1 X n T x Indicates, where M represents a transition metal element; X represents C or N; T represents a surface group, mainly -OH, -O and -F; n = 1-3. Generally speaking, MXene is obtained by selectively etching the A element in the MAX phase, and the A element is generally Al or Si. The traditional MXene preparation method uses hydrofluoric acid as an etchant. Since F- ions can form strong chemical bonds with Al or Si, selective etching can be achieved.
[0003] TiO 2 It is one of the most studied semiconductor metal oxide catalysts, with excellent light absorption efficiency and electron transfer rate. 2 Structure-activity control at the nanoscale is a research hotspot in this field. The free electrons in MXene and the hydrophilic groups at the surface end give MXene unique metallic conductive properties, and TiO can be generated in situ by oxidizing MXene. 2 , the two can form a heterojunction to enhance the transport of photogenerated carriers.
[0004] At present, there are many studies on MXene and TiO 2 Composite materials and their preparation methods have been studied to some extent. The journal Chemical Communications, Vol. 50, pp. 7387-7554, discloses a Ti 3 C 2 T x / TiO 2A preparation method, wherein Ti 3 C 2 T x The hydrothermal treatment is carried out in an autoclave at a reaction temperature of 150-250°C and a reaction pressure of 1-5 MPa. Under the action of a certain temperature and pressure, the surface Ti 3 C 2 T x Oxidized by water to TiO 2 , we get Ti 3 C 2 T x / TiO 2 Composite materials.
[0005] The invention patent application with publication number CN 111482188 A discloses a device for electrochemical preparation of MXene, including an electrolytic cell, an electrolyte and an electrode. The electrolyte is a fluorine-containing anionic liquid as an etchant, and the electrodes include a working electrode and a counter electrode made of a MAX base material. By using the working electrode as the positive electrode and applying a certain voltage, the fluorine-containing anionic liquid is ionized to produce ·F radicals, and the ·F radicals etch the Al or Si layer atoms in the MAX base material. The MXene produced by etching the MAX base material is dispersed in the electrolyte, and then the MXene material is washed and dried to obtain a two-dimensional metal carbon nitride MXene. The invention adopts a method of adding a certain voltage to the counter electrode to make the electrochemical stripping process of preparing two-dimensional metal carbon nitride MXene more gentle and easy to control.
[0006] The invention patent application with publication number CN 111482188 A discloses a Ti 3 C 2 T x / TiO 2 Composite material and preparation method thereof, wherein the layered Ti 3 C 2 T x Mxene powder is dispersed in water and stirred, and then hydrogen peroxide solution is added to the dispersion to use the strong oxidizing property of hydrogen peroxide to oxidize Ti 3 C 2 T x Mxene is oxidized at a reaction temperature of 80-120°C for 1-3 hours. Finally, the mixed solution after the oxidation reaction is subjected to ultrasonication, washed and dried to obtain Ti 3 C 2 T x Mxene composites.
[0007] The above existing technologies have great potential in the research on MXene and TiO 2 The research on composite materials has already had some foundation, but how to better combine MXene and TiO2 Further exploration and research are still needed to exploit the excellent properties of photo / electrocatalytic materials with excellent performance, optimize the reaction conditions and realize batch preparation to meet the needs of practical applications. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a Ti 3 C 2 T x / TiO 2 A method for preparing two-dimensional nanosheet materials, which can quickly, low-energy and large-scale prepare Ti with uniform structure 3 C 2 T x / TiO 2 The method has mild reaction conditions, will not destroy the material structure during the oxidation process, and can well control the degree of oxidation, and can flexibly prepare different TiO 2 Ti content 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials to match different application requirements.
[0009] A Ti 3 C 2 T x / TiO 2 The method for preparing a two-dimensional nanosheet material comprises the following steps:
[0010] (1) Ti 3 AlC 2 MAX powder is added to the hydrofluoric acid aqueous solution to make Ti 3 AlC 2 MAX powder is etched into Ti 3 C 2 T x MXene nanosheets, Ti 3 C 2 T x Dispersion of MXene nanosheets;
[0011] (2) replacing the solvent of the dispersion obtained in step (1) with water, ultrasonicating the Ti 3 C 2 T x MXene nanosheets are dispersed monolayer to obtain monolayer Ti 3 C 2 T x Dispersion of MXene nanosheets;
[0012] (3) Add the monolithic Ti obtained in step (2)3 C 2 T x A voltage is applied to the dispersion of MXene nanosheets to make the Ti 3 C 2 T x MXene nanosheets were partially oxidized to obtain Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet dispersion.
[0013] The preparation method provided by the present invention comprises three steps of etching, dispersing and oxidation in sequence, and finally obtains Ti 3 C 2 T x Uniform and smooth Ti generated in situ on MXene 3 C 2 T x / TiO 2 Two-dimensional nanosheet material. In the step (3) of the preparation method, i.e., the oxidation step, Ti 3 C 2 T x Under the external energy obtained, the Ti atomic layer on the surface of the MXene nanosheet is more likely to combine with oxygen in the aqueous solution, making the Ti 3 C 2 T x MXene nanosheets are partially oxidized to TiO 2 , realize Ti 3 C 2 T x / TiO 2 Preparation of materials.
[0014] Preferably, in step (1) of the preparation method, the mass fraction of the hydrofluoric acid aqueous solution is 20 to 60 wt %; 3 AlC 2 The dosage ratio of MAX powder to hydrofluoric acid aqueous solution is 1g:1~40mL.
[0015] According to the Ti 3 C 2 T x / TiO 2 The target diameter of the nanosheets is determined by adjusting the temperature and time of the etching.
[0016] Preferably, in step (1) of the preparation method, the etching temperature is 20-90° C., and the etching time is not less than 2 hours. Under this condition, a more suitable material sheet diameter can be obtained in the end.
[0017] In step (2) of the preparation method, the solvent is replaced with water by a commonly used replacement method, such as centrifugation, filtration, evaporation and a combination thereof.
[0018] According to step (2), the Ti content in the dispersion after the solvent is replaced with water is 3 C 2 T x The ultrasonication time was adjusted by the concentration of MXene nanosheets.
[0019] Preferably, the ultrasonic treatment time is not less than 10 min, and the ultrasonic treatment power is 50-500W.
[0020] Preferably, in step (3) of the preparation method, the single-layer Ti 3 C 2 T x Ti in the dispersion of MXene nanosheets 3 C 2 T x The concentration of MXene nanosheets is 5 mg to 5 g:1L.
[0021] In step (3) of the preparation method, the magnitude and time of the applied voltage are based on Ti 3 C 2 T x / TiO 2 TiO in two-dimensional nanosheet materials 2 Preferably, in step (3) of the preparation method, the voltage is 0.2 to 10 V and the power-on time is 1 to 180 min.
[0022] In order to better control the oxidation process, the present invention performs the single-layer Ti 3 C 2 T x The electrical conductivity of the dispersion of MXene nanosheets is limited.
[0023] Preferably, the single layer Ti 3 C 2 T x The conductivity of the MXene nanosheet dispersion is 1 to 10 S / m. Studies have found that when the conductivity of the dispersion is higher than this, it is easy to heat up and the oxidation process is too intense and uncontrollable; when it is lower than this, the oxidation process is too slow and difficult to occur.
[0024] The reaction conditions of step (3) of the preparation method are relatively mild, and the material structure will not be destroyed during the oxidation process. The degree of oxidation can be well controlled to avoid over-oxidation.
[0025] Preferably, the Ti 3C 2 T x The oxidation degree of MXene nanosheets is 3-80%, which can be flexibly prepared to obtain different TiO 2 Proportion of Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet material, and when the oxidation degree of the material is 3-80% (oxygen content is 1-32%), the oxidation process can be well controlled to match different application requirements.
[0026] The present invention also provides a Ti prepared by the above method. 3 C 2 T x / TiO 2 Two-dimensional nanosheet material. The Ti 3 C 2 T x In-situ generation of uniform and smooth TiO on the MXene surface 2 , and presents structural characteristics of large specific surface area, low degree of agglomeration, and good dispersion, and has excellent photo / electrocatalytic performance.
[0027] In the Ti 3 C 2 T x / TiO 2 Among the two-dimensional nanosheet materials, TiO 2 Ti 3 C 2 T x / TiO 2 The mass percentage is 30 to 70 wt%.
[0028] TiO 2 and MXene as photoelectron generation unit and transfer unit, respectively. 2 When the mass percentage of Ti is 30 to 70 wt%, the 3 C 2 T x / TiO 2 The photo / electrocatalytic performance of two-dimensional nanosheet materials is even better.
[0029] Preferably, the Ti 3 C 2 T x / TiO 2 The two-dimensional nanosheet material has a sheet diameter of 0.3 to 10 μm and a thickness of 1 to 10 nm.
[0030] The present invention also provides the Ti 3 C 2 Tx / TiO 2 Application of two-dimensional nanosheet materials in the preparation of water pollutant degradation materials.
[0031] Under ultraviolet light, the Ti 3 C 2 T x / TiO 2 The two-dimensional nanosheet material has a good degradation efficiency for water pollutants in a short time. More preferably, under ultraviolet light, the Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials have good degradation efficiency for antibiotics.
[0032] Compared with the prior art, the present invention has at least the following beneficial effects:
[0033] (1) Compared with Ti prepared by existing solvothermal method or high temperature oxidation method 3 C 2 T x / TiO 2 Compared with MXene nanocomposites, the present invention can obtain a monolithic dispersed Ti 3 C 2 T x / TiO 2 MXene nanosheets can well control the degree of oxidation, avoid over-oxidation, and can flexibly prepare different TiO 2 Proportion of Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials to match different application requirements.
[0034] (2) The oxidation step of the preparation method provided by the present invention is relatively mild and will not destroy the material structure during the oxidation process. 3 C 2 T x / TiO 2 The structure of two-dimensional nanosheet materials is uniform and flat. 3 C 2 T x / TiO 2 MXene and TiO in 2D nanosheet materials 2 The two have a strong interaction, the interface effect has a weak scattering effect on carriers, and can achieve efficient carrier transmission. It also presents structural characteristics of large specific surface area, low agglomeration, and good dispersion, thus having excellent photo / electrocatalytic performance.
[0035] (3) The preparation method provided by the present invention can quickly, low-energy, and large-scale prepare Ti with uniform structure. 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials.
[0036] (4) Under ultraviolet light, the Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials have a good degradation efficiency for water pollutants in a short time, especially for antibiotics. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The Ti prepared in Example 1 3 C 2 T x / TiO 2 SEM image of two-dimensional nanosheet material.
[0038] Figure 2 The Ti prepared in Example 1 3 C 2 T x / TiO 2 XPS pattern of Ti 2p in two-dimensional nanosheet materials.
[0039] Figure 3 The Ti prepared in Example 2 3 C 2 T x / TiO 2 XPS pattern of Ti 2p in two-dimensional nanosheet materials.
[0040] Figure 4 The Ti prepared in Example 3 3 C 2 T x / TiO 2 XPS pattern of Ti 2p in two-dimensional nanosheet materials.
[0041] Figure 5 The Ti prepared in Comparative Example 1 3 C 2 T x / TiO 2 SEM image of two-dimensional nanomaterials.
[0042] Figure 6 The Ti prepared in Example 2 and Comparative Example 1 3 C 2 T x / TiO 2Photoelectrocatalytic performance test results of the material. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0044] Example 1
[0045] Weigh Ti 3 AlC 2 5 g of MAX phase solid powder was added to 10 mL of 30 wt% hydrofluoric acid solution and etched at 80 °C for 2000 min. After that, Ti was obtained by filtration. 3 C 2 T x MXene nanosheets were added to 200 mL of water and ultrasonically dispersed for 180 min to obtain Ti 3 C 2 T x The conductivity of the dispersion liquid of MXene nanosheets was 2S / m. A voltage of 3V was applied to the dispersion liquid for 10 min to obtain Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials.
[0046] In this 3 C 2 T x / TiO 2 Among the two-dimensional nanosheet materials, TiO 2 Ti 3 C 2 T x / TiO 2 The mass percentage is 20.4wt%, and the sheet diameter of the material is 0.5-5μm.
[0047] Figure 1 Ti 3 C 2 T x / TiO 2 SEM image of two-dimensional nanosheet material, Figure 1 It can be seen that the Ti prepared by the method of the present invention 3 C 2 T x / TiO 2 The surface structure of two-dimensional nanosheet materials is uniform and flat.
[0048] Example 2
[0049] Weigh Ti 3 AlC 2 3 g of MAX phase solid powder was added to 20 mL of 50 wt% hydrofluoric acid solution and etched at 60 °C for 1000 min. After that, Ti was obtained by filtration. 3 C 2 T x MXene nanosheets were added to 100 mL of water and ultrasonically dispersed for 30 min to obtain Ti 3 C 2 T x The conductivity of the dispersion liquid of MXene nanosheets was 8S / m. A voltage of 8V was applied to the dispersion liquid for 80 min to obtain Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials.
[0050] In this 3 C 2 T x / TiO 2 Among the two-dimensional nanosheet materials, TiO 2 Ti 3 C 2 T x / TiO 2 The mass percentage is 59.5wt%, and the sheet diameter of the material is 0.5-5μm.
[0051] Example 3
[0052] Weigh Ti 3 AlC 2 8 g of MAX phase solid powder was added to 100 mL of 60 wt% hydrofluoric acid solution and etched at 90 °C for 1000 min. After that, Ti was obtained by filtration. 3 C 2 T x MXene nanosheets were added to 120 mL of water and ultrasonically dispersed for 80 min to obtain Ti 3 C 2 T x The conductivity of the dispersion liquid of MXene nanosheets was 5S / m. A voltage of 10V was applied to the dispersion liquid for 160 min to obtain Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials.
[0053] In this 3 C 2 T x / TiO2 Among the two-dimensional nanosheet materials, TiO 2 Ti 3 C 2 T x / TiO 2 The mass percentage is 84.9wt%. The sheet diameter of the material is 0.5-5μm.
[0054] Comparative Example 1
[0055] The same etching and dispersion steps as in Example 2 are performed, except that Ti is prepared by oxidation through calcination. 3 C 2 T x / TiO 2 Two-dimensional nanomaterials.
[0056] Compared with the method of the present invention, the calcination method tends to be completely oxidized, and the obtained Ti 3 C 2 T x / TiO 2 TiO in materials 2 The components account for the vast majority, and the morphology is uncontrollable, and TiO 2 Large particles (such as Figure 5 shown).
[0057] Figure 6 The Ti prepared in Example 2 and Comparative Example 1 were compared. 3 C 2 T x / TiO 2 The photoelectrocatalytic performance of the material. The test conditions are: using a graphite electrode as the working electrode, the electrocatalytic performance of a solution containing 100 μM ciprofloxacin was tested, and the current signal was recorded. 3 C 2 T x / TiO 2 The two-dimensional nanosheets were mixed into a solution containing 100 μM ciprofloxacin and irradiated with 50W 365nm ultraviolet light for 10 minutes. Then, the graphite electrode was used to test and record the current signal under the same conditions. The peak current intensity was used to evaluate the catalytic activity. 3 C 2 T x / TiO 2 Under ultraviolet light, the two-dimensional nanosheets can effectively degrade and remove antibiotics in a short time, and the peak current intensity is lower than that before the catalytic reaction, proving that Ti 3 C 2 T x / TiO 2 Two-dimensional nanosheets have excellent photo / electrocatalytic properties.
[0058] Depend on Figure 6 It can be seen that the catalytic efficiency of the material in Example 2 is 180% to 240% of that in Example 1. Therefore, the Ti prepared by the method of the present invention 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials have better photoelectrocatalytic performance.
[0059] Application Example 1
[0060] The Ti prepared in Example 2 3 C 2 T x / TiO 2 Two-dimensional nanosheet materials for photocatalytic degradation and removal of ciprofloxacin.
[0061] Using a graphite electrode as the working electrode, the electrocatalytic performance of a solution containing 100 μM ciprofloxacin was tested and the current signal was recorded. 3 C 2 T x / TiO 2 The two-dimensional nanosheet material was mixed into a solution containing 100 μM ciprofloxacin and irradiated with 50W 365nm wavelength ultraviolet light for 10 min. Then, a graphite electrode was used to test and record the current signal under the same conditions. It was found that the material in Example 2 had a 47.5% removal rate on the antibiotic, indicating that ciprofloxacin could be well degraded and removed in a short time.
[0062] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A Ti3C2T x The method for preparing a TiO2 two-dimensional nanosheet material comprises the following steps: (1) Add Ti3AlC2 MAX powder into hydrofluoric acid aqueous solution to etch Ti3AlC2 MAX powder into Ti3C2T x MXene nanosheets, Ti3C2T x Dispersion of MXene nanosheets; (2) replacing the solvent of the dispersion obtained in step (1) with water, and ultrasonicating the Ti3C2T x MXene nanosheets are dispersed monolayer to obtain monolayer Ti3C2T x A dispersion of MXene nanosheets, wherein the monolayer Ti3C2T x Dispersion of MXene nanosheets in Ti3C2T x The concentration of MXene nanosheets is 5 mg~5 g:1 L. The single layer Ti3C2T x The conductivity of MXene nanosheet dispersion is 1~10 S / m; (3) The monolithic Ti3C2T obtained in step (2) x A voltage is applied to the dispersion of MXene nanosheets, the voltage is 0.2-10 V, and the power-on time is 1-180 min, so that the Ti3C2T x MXene nanosheets were partially oxidized to obtain Ti3C2T x / TiO2 two-dimensional nanosheet dispersion, in which TiO2 accounts for Ti3C2T x The mass percentage of / TiO2 is 30~70 wt%.
2. The preparation method according to claim 1, characterized in that: In the step (1), the mass fraction of the hydrofluoric acid aqueous solution is 20 to 60 wt %; the dosage ratio of the Ti3AlC2 MAX powder to the hydrofluoric acid aqueous solution is 1 g: 1 to 40 mL.
3. The preparation method according to claim 2, characterized in that: The etching temperature is 20-90°C, and the etching time is not less than 2 h.
4. The preparation method according to claim 1, characterized in that: In the step (2), the ultrasonic treatment time is not less than 10 min, and the ultrasonic power is 50-500 W.
5. The preparation method according to claim 1, characterized in that: The Ti3C2T x The sheet diameter of the TiO2 two-dimensional nanosheet material is 0.3 ~ 10 μm and the thickness is 1 ~ 10 nm.
Citation Information
Patent Citations
Ti3C2Tx-TiO2 composite material as well as preparation method and application thereof
CN111482188A
Nanometer compound titanium-based photo and Fenton-like reagent and preparation method and application thereof
CN108786870A
Preparation method of carbon nanotube / titanium dioxide flexible composite film
CN114940490A